Staining in firearm barrels after experimental contact shots. (April 2017) - Schyma, C.; Bauer, K.; Brünig, J.; Courts, C.; Madea, B.
Graphical abstract: Highlights: 24 contact shots were performed, 22 generated visible staining in the barrels. Morphology and extension of staining were reproducible. Staining decreased always from the muzzle to the rear end of the barrel. DNA yield was higher in the anterior part of the barrel than in the posterior. Staining pattern was comparable to real suicide cases. Abstract: After contact shots to the head biological traces inside firearm barrels can be found. This study was conducted to simulate and to evaluate such staining. Five current handguns of four inch barrel length in the calibre .22 long rifle, 7.65 mm Browning, 9 mm Luger and .38 special were used to perform 24 contact shots on silicone coated, gelatine filled box models using the triple contrast method. The staining was documented by endoscopy and swabs gathered from both ends of the barrel were analysed by quantitative PCR. With the exception of the .22 revolver, all firearms showed distinct staining which decreased from the muzzle to the rear end of the barrel. The pattern was varied, showing droplets, elongated forms or stripes. In 14 of 24 shots, staining reached the chamber. The staining results were comparable to real suicide cases.